Can School-Based Physical Activity Projects Such as Skipping Hearts Have a Long-Term Impact on Health and Health Behavior? - Baumgartner, Lisa; Postler, Tanja; Graf, Christine; Ferrari, Nina; Haller, Bernhard; Oberhoffer-Fritz, Renate; Schulz, Thorsten (Frontiers in Public Health, 2020)
Low physical activity, limited motor skills, and an increased number of overweight or obese children are major public health problems. Numerous school-based programs try to improve physical activity and health behavior in children but investigations on sustainable effects of these programs are rare. Therefore, we examined the long-term effects of the Skipping Hearts health promotion project. 486 children (57.7% female, 9.0 ± 0.6 years at baseline) participated in this non-randomized controlled longitudinal trial within a follow-up period of 3.5 years. Of these, 286 subjects received a one-time 90-min workshop in rope skipping (Basic-Workshop) and 140 additionally received 10 lessons in rope skipping (Champion-Program), 78 students served as controls. Anthropometrics, blood pressure, motor skills, screen-based media use, self-assessment of physical fitness, and physical activity were collected at both measurement points; endurance capacity and health-related quality of life only at follow-up. Standard deviation scores of body-mass-index (η2 = 0.005) and systolic blood pressure (η2 = 0.006) decreased, while diastolic blood pressure (η2 = 0.004), motor performance (η2 < 0.001), physical fitness, subjective physical activity (η2 = 0.008), and screen-based media use (η2 = 0.001) increased without significant difference in development between groups (all p > 0.05). At follow-up, groups did not differ in endurance capacity (η2 = 0.010) and health-related quality of life (η2 < 0.001). Skipping Hearts does not affect the long-term improvement of health status, motor performance, or health behavior. To improve the effects, the project should be implemented as a daily routine in schools to force the transfer of health behavior-related knowledge. Nevertheless, the project offers a physical activity that can be performed in children's everyday life without high costs.